2021
DOI: 10.25299/kiat.2021.vol32(1).7762
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Price Earning Ratio Dan EV/EBITDA Terhadap Harga Saham Perusahaan Properti di Bursa Efek Indonesia

Abstract: Penelitian ini dilakukan pada perusahaan-perusahaan sektor properti di bursa efek indonesia dengan tujuan untuk mengetahui pengaruh Price Earning Ratio dan EV/EBITDA terhadap harga saham perusahaan properti. Analisis data penelitian ini menggunakan analisis regresi berganda dengan menggunakan program SPSS. Analisis didahului dengan analisis analisis asumsi klasik sebagai syarat untuk mengolah data analisi regresi berganda. Dari hasil penelitian diperoleh bahwa price earning ratio dan  EV/EBITD secara simultan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
1
Order By: Relevance
“…Although the effect of DER on stock prices may not be partially significant, overall, capital structure and DER value have an important impact in shaping investors' perceptions of company risk, which in turn can affect the company's stock price. The results of this study are in line with research conducted by Fahrozi & Muin (2020) which states that capital structure has no effect on stock prices. The same results shown by Horas et al (2023) found that capital structure has no effect on stock prices.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although the effect of DER on stock prices may not be partially significant, overall, capital structure and DER value have an important impact in shaping investors' perceptions of company risk, which in turn can affect the company's stock price. The results of this study are in line with research conducted by Fahrozi & Muin (2020) which states that capital structure has no effect on stock prices. The same results shown by Horas et al (2023) found that capital structure has no effect on stock prices.…”
Section: Discussionsupporting
confidence: 90%
“…According to Husna & Sunandar (2022) the stock price is the price in the real market, and is a price that is very easy to predict because it is the price of a share in the ongoing market. Furthermore, Fahrozi & Muin (2020) explain that the share price is the value of shares that occurs due to shares being traded. According to Fahrozi & Muin (2020), stock prices actually always move up and down following the demand and supply that occurs in the stock market.…”
Section: Literature Review Stock Pricementioning
confidence: 99%
See 2 more Smart Citations
“…Peningkatan DER bertujuan untuk menjaga kestabilan arus kas terutama masa pandemi. Dalam ketentuan fasilitas kredit, seluruh perusahaan farmasi yang digunakan masih dibawah dari rata-rata sehingga DER tidak berpengaruh signifikan terhadap return saham (Fahrozi & Muin, 2020).…”
Section: Pengaruh Struktur Modal Terhadap Return Sahamunclassified